COVID‐19 and COVID‐19 vaccine‐related dermatological reactions: An interesting case series with a narrative review of the potential critical and non‐critical mucocutaneous adverse effects related to virus, therapy, and the vaccination - Arash Pour Mohammad; Farzaneh Mashayekhi; Farnoosh Seirafianpour; Milad Gholizadeh Mesgarha; Azadeh Goodarzi (Clinical Case Reports, 2022)
Abstract This narrative review article was conducted to lay out a summarized but exhaustive review of current literature over mucocutaneous manifestations in 4 dimensions of SARS‐CoV‐2 pandemic: virus itself, treatment‐related, vaccine‐induced, and alteration of chronic dermatologic diseases following infection. Virus and vaccine‐related were mainly self‐limited and non‐severe. Treatment‐related reactions could be life‐threatening.